2008
DOI: 10.1212/01.wnl.0000298691.71637.96
|View full text |Cite
|
Sign up to set email alerts
|

Mesopontine cholinergic neuron involvement in Lewy body dementia and multiple system atrophy

Abstract: Loss of cholinergic pedunculopontine tegmental nuclei/laterodorsal tegmental nuclei neurons occurs in both dementia with Lewy bodies and multiple system atrophy but is probably not the primary mechanism of REM sleep behavior disorder in these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 22 publications
6
66
0
Order By: Relevance
“…30 Ascending cholinergic pathways from the pedunculopontine nucleus and laterodorsal tegmental nuclei are involved in arousal. 31 The loss of these projections has been described in DLB, but neuronal counts did not correlate with sleep disturbances or fluctuations. DLB is associated with greater attentional deficits compared with AD 32 ; however, loss of attentional control is also an early finding in AD.…”
mentioning
confidence: 92%
“…30 Ascending cholinergic pathways from the pedunculopontine nucleus and laterodorsal tegmental nuclei are involved in arousal. 31 The loss of these projections has been described in DLB, but neuronal counts did not correlate with sleep disturbances or fluctuations. DLB is associated with greater attentional deficits compared with AD 32 ; however, loss of attentional control is also an early finding in AD.…”
mentioning
confidence: 92%
“…33 Besides the dopaminergic neurons of substantia nigra, the cholinergic neurons in the dorsal mesopontine nuclei, specifically the pedunculopontine tegmental and lateral dorsal tegmental nuclei, are involved with the LB-related pathology with significant loss of cholinergic neurons. 33,35 Degeneration in the dorsal mesopontine region may involve other neurotransmitter systems including the noradrenergic system because of degeneration in the locus coeruleus and the serotonergic system via damage to the dorsal raphe nu- clei. 36,37 The mesopontine nuclei are also affected in AD, [37][38][39] although there is some evidence that they are more affected in DLB than in AD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown hypocretinergic cell loss in the lateral hypothalamus of patients with Parkinson's disease, which could contribute to the 'narcoleptic-like' features in PDD and DLB [30] . The pathology of cognitive fluctuations has been suggested to be localized in the isodendritic core, a small group of nuclei in the brainstem and basal forebrain that forms part of the reticular activating system and includes the locus coeruleus, raphe nuclei and the basal nucleus of Meynert [31] and more recently specifically to the pedunculopontine and laterodorsal tegmental nuclei [32] .…”
Section: Discussionmentioning
confidence: 99%